RECENT TECHNOLOGICAL ADVANCES IN WORLD OF SPORTS: DEVELOPING SPORTS ERA - Chackuparambil, Jaya John (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Today, the application of various technologies requires new skills from students and teachers. The student must demonstrate motor skills and use technology primarily through self-learning. It is necessary to learn to manage the organization of activities through the use of various devices. Physical education curricula and health programs are being developed to provide students with better opportunities instead of traditional gym classes. Technology has the potential to facilitate more effective high school teaching and provide high school teachers with key information that can be used to influence their work. Teachers can also conduct video interviews to document student impressions of exercise and motor learning. The rapid development of electrical technology has had a major impact on the education systems of the world. Thanks to technology, especially mobile technology, physical education teachers now have a variety of tools to explore and improve their students’ physical skills. The list includes video analytics, wearable technology, fitness apps, gaming systems, virtual classrooms and monitors and tracking devices. Sports technology has come to the fore in recent years due to the rise of indoor sports (eg table tennis, chess, etc.) and outdoor sports (eg athletics, rugby, cricket and tennis). The growing adoption of apparel among athletes in various countries is likely to boost the growth graph of the sports technology market upwards. In addition, the widespread adoption of the Internet of Things in the sports sector has played an important role in the engagement of fans and the physical growth of players.